PROFIL KONDISI FISIK ATLET DAYUNG KLUB DAYUNG KABUPATEN BANDUNG BARAT - Opin, Opin (Journal of Physical Education and Sport Science, 2024)
Physical Condition Profile of Rowing Athletes Rowing Club West Bandung Regency, Physical Education, Health, and Recreation Study Program (PJKR), 2022. Rowing is a measurable sport with a predominantly aerobic energy system. However, other physical components also become the carrying capacity for the achievement of rowing athletes. Therefore, this study aims to determine the level of physical condition of rowing athletes in rowing clubs in Bandung Regency. This research is a quantitative descriptive study with a survey approach. The sample in this study were male rowing athletes at the Bandung Regency rowing club with the age of 17 years as many as 10 people. Data collection techniques used physical component tests and practices, namely, aerobic endurance test using multistage fitness test, flexibility test using sit and reach test, strength test using 1RMbenchpress test, and power test using vertical jump test. The results of this study indicate that the athlete's endurance level is in the sufficient category with a frequency percentage of 40%, the athlete's flexibility level is in the sufficient category with a frequency percentage of 40%, the athlete's strength level is in the less category with a frequency percentage of 40%, The athlete's leg power is in the very poor category with a frequency percentage of 40%, and the overall level of the athlete's physical condition is in the sufficient category with a frequency percentage of 70%.